Pemanfaatan Citra Landsat Untuk Klasifikasi Tutupan Lahan Lanskap Perkotaan Kota Palu - ACHSAN, ANDI CHAIRUL (Jurnal Arsitektur Lansekap; Vol.3, No.1, April 2017DO - 10.24843/JAL.2017.v03.i01.p07, 2017)
ABSTRACT The Use of Landsat Image For Land Cover Classification On Urban Landscape Of Palu City One of effort that can be done for knowing urban development is with seeing land cover information. By land cover map can be kown the information of kind of land cover, area of each land cover and thedistribution of the use of space on the region. Satellite image is one of media that can be used for obtaining the information of land cover. This research purpose was for analysing the use of landsat image for determining the land cover classification on urban landscape using geographic information system. Classification proces of satellite image was started by merging band and cropping image, geometric correction and classification using image classification and the data from classification was converted from raster data to the vector data. From conversion result was obtained information of land cover class for every kind of land cover. Results of land cover class consist of building with area 3110, 79 ha, forest with area 1689,34 ha, farm with area 386,67 ha, and water body 830,35 ha. Keywords : landsat image, classification, land cover